A large radiolucent lesion with impacted teeth: was it an ameloblastoma or a dentigerous cyst? a case report - Rahmadini, Galih; Sam, Belly; Sitam, Suhardjo; Azhari, Azhari; Sadputranto, Seto Adiantoro (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: This case report aims to describe a large radiolucent lesion associated with an impacted tooth from CBCT radiographs. Case Report: A 19-year-old woman was referred to have a CBCT examination in the dentomaxillofacial radiology unit in Dental Hospital Universitas Padjadjaran with swelling on the palatal side of the face and a lump on the gum at the upper right unerupted canine and premolar. The CBCT examination results showed impacted teeth 13 and 14 with a large radiolucent lesion with a well-defined and corticated border surrounding teeth 13 and 14, expanding into the maxillary sinus and nasal cavity. Oral hygiene was in good condition. The facial profile looked asymmetrical. Conclusion: Based on the CBCT result in terms of location and radiographic feature, this extensive radiolucent lesion led to a suspect radiodiagnosis of the ameloblastoma. Histology examinations are required to establish a definitive diagnosis. A cyst wall lined with odontogenic squamous epithelium was confirmed in the histology result examination.